2006
DOI: 10.1373/clinchem.2006.069575
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of B-Type Natriuretic Peptide (BNP) and Amino-Terminal proBNP in a Large Population of Patients with Chronic and Symptomatic Heart Failure: The Valsartan Heart Failure (Val-HeFT) Data

Abstract: on behalf of the Val-HeFT InvestigatorsBackground: The B-type or brain natriuretic peptides (BNP) and the amino-terminal probrain natriuretic peptide (NT-proBNP) are good markers of prognosis and diagnosis in chronic heart failure (HF). It is unclear, however, whether differences in their biological characteristics modify their clinical correlates and prognostic performance in HF. This work aimed to provide a direct comparison of the prognostic value of BNP and NTproBNP in patients with chronic and stable HF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
219
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(254 citation statements)
references
References 42 publications
22
219
1
12
Order By: Relevance
“…BNP is secreted primarily by cardiac myocytes in response to increase in LV wall stress, resulting in myocyte stretch, and the BNP level shows good correlation with LV end‐diastolic pressure. BNP levels are associated with HF severity across the spectrum of HF stages 9, 10, 11. In the current study, the BNP levels showed a significantly independent predictive value for poor prognosis in patients with HFrEF, HFpEF, and HFrlEF.…”
Section: Discussionsupporting
confidence: 54%
“…BNP is secreted primarily by cardiac myocytes in response to increase in LV wall stress, resulting in myocyte stretch, and the BNP level shows good correlation with LV end‐diastolic pressure. BNP levels are associated with HF severity across the spectrum of HF stages 9, 10, 11. In the current study, the BNP levels showed a significantly independent predictive value for poor prognosis in patients with HFrEF, HFpEF, and HFrlEF.…”
Section: Discussionsupporting
confidence: 54%
“…Neither biomarker predicted MI. In the Valsartan Heart Failure Trial (Val‐Heft), NT‐proBNP proved superior to BNP in predicting a composite of morbidity and mortality and HF hospitalization in chronic HF patients; however, the incremental discriminatory value of NT‐proBNP versus BNP was small 30. In our study of ACS patients with type 2 diabetes mellitus, both natriuretic peptides had comparable predictive strength in all outcomes studied (death, cardiovascular death, MI, HF, and stroke), albeit NRI and Integrated Discrimination Index values increased slightly more with BNP across all outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…У пациентов с хронической СН BNP может пред-сказать будущие сердечные события и госпитализации [29][30][31]. Результаты исследования Val-HeFT, описанные Masson et al [29], показали, что BNP и NT-proBNP являют-ся самыми сильными предикторами смертности и госпи-тализации по поводу СН.…”
Section: прогнозирование заболеваний пациента на основе анализа генетunclassified
“…Результаты исследования Val-HeFT, описанные Masson et al [29], показали, что BNP и NT-proBNP являют-ся самыми сильными предикторами смертности и госпи-тализации по поводу СН. Увеличение уровня BNP на 50 нг/мл от исходного уровня имело высокий риск по сравнению с объединенным анализом Doust et al, что продемонстрировало увеличение смертности на 35% с увеличением на 100 пг/мл от исходного уровня [30].…”
Section: прогнозирование заболеваний пациента на основе анализа генетunclassified